2015
DOI: 10.1002/oby.21202
|View full text |Cite
|
Sign up to set email alerts
|

Hunger and satiety responses to high‐fat meals of varying fatty acid composition in women with obesity

Abstract: Objective: Determine subjective and physiological appetite responses and ad libitum intake to high-fat (HF) meals rich in either monounsaturated (MUFAs), polyunsaturated (PUFAs), or saturated fatty acids (SFAs) in women with obesity. Methods: In this single-blind crossover study, three HF meals (70% of energy) rich in MUFAs, PUFAs, or SFAs in 16 women with obesity were tested. At each visit, anthropometrics and a fasting blood sample were collected. Participants then consumed one of the HF meals, and postprand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 40 publications
3
27
1
Order By: Relevance
“…In fact, participants reported that they enjoyed consuming the assigned muffins. A potential reason for the greater weight loss in PUFA than in MUFA subjects is suggested by greater increases in the anorexigenic hormone peptide YY after PUFA intake compared to MUFA or SFA (36). In addition to the 4.6% reduction in body weight, PUFA enrichment continued to be associated with improved FMD, TG and a trend toward reduced DBP compared to MUFA assignment, even after controlling for weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, participants reported that they enjoyed consuming the assigned muffins. A potential reason for the greater weight loss in PUFA than in MUFA subjects is suggested by greater increases in the anorexigenic hormone peptide YY after PUFA intake compared to MUFA or SFA (36). In addition to the 4.6% reduction in body weight, PUFA enrichment continued to be associated with improved FMD, TG and a trend toward reduced DBP compared to MUFA assignment, even after controlling for weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic feeding behavior and nutritional status have been proposed for the elevation of ghrelin in AN although the exact mechanism remains elusive [40]. It is worth noting that in a study examining three types of high fat meal on physiological markers of hunger and satiety, a meal rich in PUFAs or monounsaturated fatty acids (MUFAs) reduced ghrelin significantly more than a meal rich in saturated fatty acids (SFAs) [42]. Determining the differential effects n-3 PUFAs and n-6 PUFAs exert on physiological markers of hunger (such as ghrelin) and eating behavior is an important next step to further our knowledge on therapeutic values of PUFAs in order to “personalize” such treatment for AN and other eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggest that POMC expression by GLP-1 stimulation could be higher in CHO-rich meal group than in fat-rich meal, which is in accordance with our results. There are more evidence that fatty acid composition differentially affected GLP-1 response, but different GLP-1 responses among different diet composition groups was not associated with changes in subjective appetite ratings or changes in energy intake when alterations were made from an acute HF meal to fatty acid composition [16], and GLP-1 response in SFA-rich diet group tended to be somewhat higher than in PUFA-rich diet group at 150 minutes after eating (Fig. 1 of [16]).…”
mentioning
confidence: 99%
“…There are more evidence that fatty acid composition differentially affected GLP-1 response, but different GLP-1 responses among different diet composition groups was not associated with changes in subjective appetite ratings or changes in energy intake when alterations were made from an acute HF meal to fatty acid composition [16], and GLP-1 response in SFA-rich diet group tended to be somewhat higher than in PUFA-rich diet group at 150 minutes after eating (Fig. 1 of [16]). These results could be in agreement with ours although GLP-1 response was very variable depending on the time period after eating [1516].…”
mentioning
confidence: 99%
See 1 more Smart Citation